Penerapan Digital Marketing Dan Peran Content Creator Pada Media Sosial Guna Meningkatkan Brand Awareness PT. Otak Kanan Surabaya - Nada Fitra Nabila; Oktifani Winarti (Jurnal Informasi Pengabdian Masyarakat, 2023)
Digital marketing has become one of the effective strategies to increase the company's brand awareness. With the rapid development of social media, many companies are utilizing social media to market their products. To attract audiences, interesting content is needed and follow current trends. PT. Otak Kanan is a company engaged in the creative industry that has less than optimal branding problems. Therefore, this research aims to find out, observe, provide solutions, and dive directly using the active participation observation implementation method in creating content marketing to increase brand awareness. Social media also plays a key role in digital marketing for brand awareness. The results show that creating interesting creative content on social media platforms such as Instagram and TikTok is able to increase the company's brand awareness.